Analisis Hubungan Motivasi Belajar dengan Kemampuan Pemecahan Masalah Siswa Kelas XII pada Materi Sistem Persamaan Linear Dua Variabel di SMK Negeri 1 Boronadu - Sentosa Giawa; Firman Pangaribuan; Hardi Tambunan (Journal on Education, 2024)
The ability to solve problems is one of the cognitive abilities in mathematics that students need to master. To support mastery of problem solving, students need motivation to learn. This research aims to determine the relationship between learning motivation and students' mathematical problem solving abilities. The research method used is a correlational method with a quantitative approach. The population of this study were all class XII students at SMK Negeri 1 Boronadu and the sample chosen was class XII majoring in TKJ, totaling 15 students. The instrument used in this research is a test to measure problem-solving ability in the form of an explanation of 3 questions, while the non-test instrument to measure the level of learning motivation is in the form of a questionnaire scale. Data were analyzed using the Pearson product moment correlation test. The results of this research indicate that at a significance level of 0.05 there is a relationship between learning motivation and students' problem solving abilities. Apart from that, the linear regression equation Y = 12.964+0.422X is obtained, which means that for every additional 1 learning motivation value, mathematical problem solving ability increases by 0.422.